Dermoscopy of Grover's disease: Variability according to histological subtype. Issue 8 (19th February 2016) - Errichetti, Enzo; De Francesco, Vincenzo; Pegolo, Enrico; Stinco, Giuseppe
Abstract: Distinguishing Grover's disease from other papular dermatoses is often a troublesome task. According to two relatively recent case reports, dermoscopy may be useful in assisting the diagnosis of such a disorder by showing a peculiar pattern. The aim of this study was to evaluate the dermoscopic features of Grover's disease in a larger series of patients and correlate dermoscopy with histopathological findings. Seven patients with histopathologically confirmed Grover's disease were included in the study, with three of them displaying a Darier‐like histology and the remaining four cases having a spongiotic histological pattern. The results of our study suggest that Grover's disease may display different features according to the histological subtype, with a central star‐shaped/branched polygonal/roundish‐oval brownish area surrounded by a whitish halo being characteristic of the Darier‐like histological subtype and whitish scales over a reddish‐yellowish background being characteristic of the spongiotic histological subtype.